1998
DOI: 10.1159/000046293
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Crystal Interactions and Kidney Stone Formation

Abstract: Background: Renal tubular fluid in the distal nephron is supersaturated with calcium and oxalate ions that nucleate to form crystals of calcium oxalate monohydrate (COM), the most common crystal in renal stones. How these nascent crystals are retained in the nephron to form calculi in certain individuals is not known. Methods: The results of experiments conducted in this and other laboratories that employ cell culture model systems to explore renal epithelial cell-urinary crystal interactions are described. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 39 publications
(78 reference statements)
1
56
0
Order By: Relevance
“…Third, endocytosis occurred as early as 30 minutes after exposure of the cells to the crystals. 17 During endocytosis, the formed cell-crystal complexes appeared to separate from the monolayer, and large gaps appeared at cell-cell contact regions. 18 Changes in Vero cell viability during crystal adhesion Figure 4A shows the changes in cell viability during the process of adhesion between Vero cells and submicron COD.…”
Section: Morphology Change In Vero Cells Before and After Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Third, endocytosis occurred as early as 30 minutes after exposure of the cells to the crystals. 17 During endocytosis, the formed cell-crystal complexes appeared to separate from the monolayer, and large gaps appeared at cell-cell contact regions. 18 Changes in Vero cell viability during crystal adhesion Figure 4A shows the changes in cell viability during the process of adhesion between Vero cells and submicron COD.…”
Section: Morphology Change In Vero Cells Before and After Injurymentioning
confidence: 99%
“…17 Many studies showed that cell injury could be triggered by crystal endocytosis. 17,18,34 COM crystals could be actively endocytosed individually or as aggregates by Madin-Darby canine kidney cells. 22 The crystals were intermingled with microvilli and cilia at the surface, and adjacent cells were structurally altered.…”
Section: Adhesion Between Vero Cells In the Injury Group And Codmentioning
confidence: 99%
“…Urinary macromolecules, e.g. glycoproteins, proteins and glycosaminoglycans, adherent or bound to the crystals, counteract both crystal aggregation and crystal growth [12,20], and macromolecules are also important for the adherence of crystals to the tubular cells and for crystal-cell interaction [21,22].…”
Section: Epidemiological Considerationsmentioning
confidence: 99%
“…The adhesion of COM crystals to epithelial cells stimulates the expression of several groups of genes, including transcription factors, growth factors, and genes involved in proliferation of epithelial cells and in remodeling of the extracellular matrix [35]. Each of these cellular events may be regulated by a different set of extracellular signal transducers.…”
Section: Introductionmentioning
confidence: 99%